Paucity of Health Data in Africa: An Obstacle to Digital Health Implementation and Evidence-Based Practice - Sulaiman Muhammad Musa; Usman Abubakar Haruna; Usman Abubakar Haruna; Emery Manirambona; Gilbert Eshun; Dalhatu Muhammad Ahmad; David Adelekan Dada; Ahmed Adamu Gololo; Shuaibu Saidu Musa; Abdulafeez Katibi Abdulkadir; Don Eliseo Lucero-Prisno III (Frontiers Media S.A., 2023)
Background: Among the numerous challenges that Africa faces in improving its healthcare systems, the paucity of health data stands out as paramount. This study aims to examine the challenges related to the paucity of health data in Africa and its impact on the implementation of digital health and evidence-based practice. The findings of the study reveal that health data availability in Africa is both limited and frequently of poor quality. Several factors contribute to this concerning situation, encompassing inadequate infrastructure, a shortage of resources, and cultural barriers. Furthermore, the available data, despite its limitations, is often underutilized due to a lack of capacity and expertise in data analysis and interpretation.Policy Options and Recommendations: To improve healthcare delivery in Africa, we recommend implementing novel strategies for data collection. It's important to recognize that effective information technology service is crucial for enhancing healthcare delivery, and a holistic approach is necessary to achieve this.Conclusion: This brief presents information to help policymakers develop long-term solutions to Africa's health data poverty. Taking action based on this evidence can assist in addressing the problem.